STUDENT DEMOTIVATION IN LEARNING ENGLISH: Demotivasi Siswa Dalam Pembelajaran Bahasa Inggris - Salamun, Amita; Taufik, Taufik; Mukaddar, Kiky Anasya (Uniqbu Journal of Social Sciences, 2023)
Students were less enthusiastic and eager to learn English. This study aims to determine the internal and external factors of MTs Negeri 1 Baubau students regarding demotivation in learning English. Data was collected with research instruments in the form of observation, interviews, and document studies. The data obtained was analyzed through three stages, namely data reduction, data presentation, and verification. The results of the study show that there are several internal factors that cause students not to be motivated to learn English, namely low interest in learning English, students also find it difficult to learn English and they often feel bored when learning English and external factors that cause students to be unmotivated for learning English is the teacher's attitude when teaching, namely the lack of interaction between the teacher and students in the school environment, students feel that the teacher's teaching style is still unattractive, students have difficulty doing assignments due to a lack of English vocabulary, the influence of classmates who mostly dislike English, the lack of availability of books in the library and the low interest in reading students, and the last is the lack of support or attention from the family towards the student learning process.